2020
DOI: 10.12997/jla.2020.9.1.162
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of High-Dose Atorvastatin in Moderate-to-High Cardiovascular Risk Postmenopausal Korean Women with Dyslipidemia

Abstract: Objective Postmenopausal women show a more atherogenic lipid profile and elevated cardiovascular risk compared to premenopausal women. The aim of this study was to investigate the efficacy and safety of high-dose atorvastatin on the improvement of the blood lipid profile of postmenopausal women in Korea. Methods This study is a prospective, open-label, single-arm clinical trial that was conducted in 3 teaching hospitals. Postmenopausal women with a moderate-to-high card… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
3
8
0
Order By: Relevance
“…Still, there were no statistically significant differences between the groups. These relatively small and nonsignificant changes in TG, HDL-C, and Apo-A1 levels were also similar to those of previous studies [ 35 , 37 , 38 ]. Atorvastatin 20 was more efficient than atorvastatin 10 mg in for the very high-risk group patients in achieving target LDL-C and non-HDL-C levels.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Still, there were no statistically significant differences between the groups. These relatively small and nonsignificant changes in TG, HDL-C, and Apo-A1 levels were also similar to those of previous studies [ 35 , 37 , 38 ]. Atorvastatin 20 was more efficient than atorvastatin 10 mg in for the very high-risk group patients in achieving target LDL-C and non-HDL-C levels.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, treatments with atorvastatin 10 and 20 mg over a 12-week period were compared to explore the dose of atorvastatin that is more appropriate in high-risk Asian patients in terms of efficacy, safety, and cost-effectiveness. As reported by earlier studies regarding the effectiveness and safety of atorvastatin in Asian patients even at a high dose [ 35 , 36 ], the present study also demonstrated that atorvastatin effectively improved various lipid profiles without increasing the rate of ADRs. The percentage change in LDL-C levels after atorvastatin therapy was comparable to that reported by previous studies [ 35 , 37 , 38 ].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Statin treatment is relatively safe for patients with dyslipidemia and cardiovascular diseases [ 6 , 7 , 8 ]. Specifically, statin treatment often causes adverse skeletal muscle symptoms, including skeletal muscle pain, weakness, and fatal rhabdomyolysis [ 9 ], which are associated with major pathological changes, such as the elevation of creatine kinase (CK) levels [ 10 ], reduction of muscular strength, muscle weakness [ 11 ], induction of apoptosis [ 12 ], and mitochondrial dysfunction [ 13 ] in skeletal muscles.…”
Section: Introductionmentioning
confidence: 99%